Radial line slot array (RLSA) antenna design for point to point communication at 5.8 GHz - Ul Islam, Md. Rafi (2007)
A new type of linearly polarized Radial Line Slot Array (RLSA) antenna developed by FR-4 substrate is proposed for outdoor WLAN point to point application. The WLAN is based on the IEEE 802.1 la standard and the operating frequency range is the upper UNII band (5.725-5.875) GHz. The frequency range is use for point to point microwave link. Point to point microwave link is a wireless connection between one point to another point. Before this all the research has been conducted on conventional RLSA antenna developed by polypropylene and two layers copper foil. But these antennas are quite expensive and difficult to develop. Typically the point to point system uses standard parabolic dish antenna. However the uses of these antennas have some disadvantages such as aperture blockage. To overcome this drawback, a new antenna design is proposed and investigated. Therefore, this research was conducted in order to design and develop antenna with aesthetic, low cost, high performance, durable and flat antenna that could be utilized in point to point microwave link. The development of linearly polarized radial line slot antenna (RLSA) with experimental performance is presented. The method is beam squinted design. The prototype development processes included specification definition, selection of the cavity's dielectric material and construction of prototype. The production of prototypes is divided into two stages. The first stage is to simulate the radiation pattern of slot arrangement at operating frequency. The second stage is to produce the prototype and to evaluate its performance. The prototype of RLSA has been successfully constructed and tested for outdoor WLAN point to point application